Transdermal delivery of glyceryl trinitrate: clinical applications in acute stroke. (3rd March 2020) - Appleton, Jason P.; Krishnan, Kailash; Bath, Philip M.
ABSTRACT: Introduction: Glyceryl trinitrate (GTN), a nitric oxide donor, is a candidate treatment for the management of acute stroke with hemodynamic and potential reperfusion and neuroprotective effects. Areas covered: Here we discuss the evidence to date from clinical trials and present and future possibilities for the clinical application of transdermal GTN in acute stroke. When administered as a transdermal patch during the acute and subacute phases after stroke, GTN was safe, lowered blood pressure, maintained cerebral blood flow, and did not induce cerebral steal or alter functional outcome. However, when given within the hyperacute phase (<6 h of stroke onset), GTN reduced death and dependency, death, disability, cognitive impairment, and mood disturbance, and improved quality of life. However, in a large prehospital trial with treatment within 4 h, GTN did not influence clinical outcomes. Expert opinion: Transdermal GTN is an easy to administer BP-lowering therapy, which is safe when given after 2 h of stroke onset, may improve outcome when initiated within 2–6 h, but should be avoided (outside of a clinical trial) in the ultra-acute period within 2 h of stroke onset. Further research needs to investigate the mechanisms of benefit or harm in ultra/hyperacute stroke patients.